Fuchs’ Heterochromic Iridocyclitis in an Italian Tertiary Referral Centre: Epidemiology, Clinical Features, and Prognosis - Massimo Accorinti; Giovanni Spinucci; Maria Pia Pirraglia; Simone Bruschi; Francesca Romana Pesci; Ludovico Iannetti (Journal of Ophthalmology)
Purpose. To study epidemiology, clinical findings and visual prognosis of patients with Fuchs’ Heterochromic Iridocyclitis (FHI). Methods. A retrospective analysis was performed on 158 patients with FHI. Thirty-five patients were observed only once; the remaining 123 had a mean follow-up of 30.7 months (50 of them had a mean follow-up of 63.5 months) and in those we assessed complications, medical and surgical treatment, and long-term visual prognosis. Results. Average age at uveitis diagnosis was 27.2 years and 18.3% of patients were children. Blurred vision (54.5%) and floaters (40.5%) were the most frequent presenting symptoms. Small to medium-sized keratic precipitates (95.6%), iris atrophy (86.8%), and vitreous opacities (91.2%) were the most common signs; the prevalence of cataract and IOP increase was 63.5% and 20.1%, respectively, and their incidence was 0.1 and 0.06 eye/year. Significant risk factor for visual loss was IOP increase at presentation (p=0.02). At final examination 98% of the eye had a visual acuity ≥ 0.6, and topical (p<0.001) and systemic (p<0.001) corticosteroids therapy were used less frequently than before referral. Conclusions. FHI has a good visual prognosis, despite the significant incidence of cataract and glaucoma. A correct and prompt diagnosis might avoid unnecessary therapies and provide excellent visual outcomes.